The Effects of Life Style and Exercise Habits on Bone Mineral Density in Postmenopausal Period of Women - Derya Demirbağ; Semra Güldiken; Mevlüt Türe; Ferda Özdemir (Galenos Yayinevi, 2003)
Life style, habits, diet features and chronic diseases of women may possibly cause bone mineral density changes in postmenopausal period. In our study, we aimed to investigate whether there was any association between bone mineral densities (BMD) and education, job, clothing, sunbathing and exercise habits in women and its contribution to osteoporosis risk. 200 women (average age= 58,75 ± 8,75) refered to osteoporosis outpatient clinic were included in this study. Age, menopausal age, menopausal duration, job, education, sunbathing, clothing and exercise habits of subjects were recorded. BMD measurements were performed with DEXA. Positive corelation was found between woman with education level and femoral neck (r=0.151, p=0.032) and wards triangle (r=0.208, p=0.003) BMD. There was a significant difference in femoral neck BMD between modern and covered clothing (p=0.021). There were significant differences in L3 (p=0.034) and femoral neck (p=0.009) BMD between exercising and not exercising women. The comparisons between exercise duration and BMD values were investigated. In the regularly exercised group, positive corelation was found between exercise duration and femoral neck BMD. We concluded that exercise duration, clothing and sunbathing in women were effective on increasing BMD values.